Soft body armour. Issue 2 (3rd April 2019) - Mawkhlieng, Unsanhame; Majumdar, Abhijit
Abstract: A detailed and timely progress of soft body armour against stab and ballistic impact is presented in this monograph. The classification and the evolution of body armour is briefly presented, demonstrating the change of material choice with time. The energy absorption capacity of soft body armour and the mechanisms by which this energy is absorbed or dissipated are dependent upon various parameters and a detailed review is highlighted to best understand the material and structural influence. Various stab and ballistic resistance standards against which armour is currently evaluated are presented in detail. Additionally, the different techniques used to evaluate the performance of armour, from a single layer high-performance fabric to a full armour panel assembly are explained in depth, focusing on yarn pull-out, dynamic impact and ballistic test. Further, different approaches adapted to improve the impact or ballistic response of a high-performance fabric used for soft armour panels is reported exhaustively, with special attention drawn to the application of natural rubber, shear thickening fluid (STF) and surface modification of fibre. Among these, the use of STF is given greater importance, minutely exploring the mechanism of shear thickening, the factors affecting shear thickening behaviour and the methods adopted to improve the thickening or viscosity of STFs. Furthermore, emphasis is laid upon the failure mechanisms of a single high-performance fabric to low velocity impact and of an armour panel to high velocity impact, both for neat and STF treated structures. Moreover, the effectiveness or applicability of soft body armour is valid only when certain conditions are met, a list of which is concisely outlined. Finally, with new techniques and approaches being explored at research level, a futuristic and revolutionalised concept of soft body armour is anticipated- the application of nanomaterials, the use of smart textiles and the concept of biomimetics in armour design.